2017
DOI: 10.1093/annonc/mdw555
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among 21st century blood transfusion recipients

Abstract: BackgroundSome carcinogenic viruses are known to be transmissible by blood transfusion. Intensive viral screening of transfused blood now exists in most countries. In the UK, high-sensitivity nucleic acid amplification tests for hepatitis C virus were introduced in 1999 and it was thought that this would reduce, and possibly eliminate, transfusion-related liver cancer. We aimed to investigate cancer risk in recipients of blood transfusion in 2000 or after.MethodsA total of 1.3 million UK women recruited in 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
(23 reference statements)
1
21
0
1
Order By: Relevance
“…This raises concerns of either reverse causality (lymphoma causing anemia) or confounding by indication of medical conditions associated with both risk of transfusion and NHL. In the Million Women Study [21], history of blood transfusion after 2000 (modern era of intense viral screening) was ascertained from electronic hospital records. In that study, there was also an elevated risk of NHL <5 years after transfusion (RR=4.69; 95% CI 3.79-5.82).…”
Section: Discussionmentioning
confidence: 99%
“…This raises concerns of either reverse causality (lymphoma causing anemia) or confounding by indication of medical conditions associated with both risk of transfusion and NHL. In the Million Women Study [21], history of blood transfusion after 2000 (modern era of intense viral screening) was ascertained from electronic hospital records. In that study, there was also an elevated risk of NHL <5 years after transfusion (RR=4.69; 95% CI 3.79-5.82).…”
Section: Discussionmentioning
confidence: 99%
“…13,21 Other causes should be considered including lifestyle habits of alcohol, smoking, and the presence of occult cancer foci. 8,12,22 In another study, the increased cancer risk was mainly attributed to the transfer of carcinogenic infectious agents like EBV, HIV, and HCV. This explains why there was an increased risk for specific cancers, such as lymphoma and liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…13 All studies that investigated the risk of cancer after blood transfusion found that there is a temporal dependent risk association. [11][12][13][14][15]20 The risk decreases over time and after a specific period, there was no risk of cancer. This was explained as a reverse causation relationship and that the increased risk of cancer after transfusion does not necessarily mean that the transfusion is the cause of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…5 éven túl azonban szignifikánsan több májcarcinomát (1,45×-es rizikó), kissé több myelomát és nagyobb számú non-Hodgkinlymphomát (1,74×-es rizikónövekedés) találtak. Ha kizárólag a csípőprotézis miatt transzfundáltakat nézték, ez az arány akkor is ugyanennyi volt [27].…”
Section: Daganatok éS Transzfúziók Kérdéseunclassified